Mechanical, structural and barrier properties of starch-based film reinforced with cellulose microfibres extracted from midribs of Musa Saba' - Awang Wahab, D.N.; Siddique, M.B.M.; Khairuddin, N.; Chew, J.J.; Su, H.T. (Rynnye Lyan Resources, 2024)
Starch-based films have poor mechanical strength and high-water vapour permeability. This research aimed to develop biopolymeric films that contain wheat starch, glycerine, reinforcing agent, and cellulose microfibres (CMR) at 0.5 and 1 wt.%, through a casting technique. The CMR was derived from chemically treated banana midrib residues (Musa Saba' sp.). The effect of CMR filler on structural, mechanical and barrier properties was studied. The results show that the incorporation of CMR into the starch-based films has improved the fragility of films. The increased concentration of CMR has contributed to an improvement in film thickness (3.5–7.6%), tensile strength (8.1–55.4%), Young’s modulus (4.2–32.5%), and vapour barrier permeability (12–17.5%). The good compatibility and homogenous dispersion of CMR fillers were corroborated using FESEM (EDX). In conclusion, CMR fillers have improved the properties of starch-based films and potential to be used as reinforcing elements in various polymer composites.